Pre-arranged building block approach for the orthogonal synthesis of an unfolded tetrameric organic–inorganic phosphazane macrocycle - Sim, Ying (2023)
Inorganic macrocycles remain challenging synthetic targets due to the limited number of strategies reported for their syntheses. Among these species, large fully inorganic cyclodiphosphazane macrocycles have been experimentally and theoretically highlighted as promising candidates for supramolecular chemistry. In contrast, their hybrid organic–inorganic counterparts are lagging behind due to the lack of synthetic routes capable of controlling the size and topological arrangement (i.e., folded vs unfolded) of the target macrocycle, rendering the synthesis of differently sized macrocycles a tedious screening process. Herein, we report—as a proof-of-concept—the combination of pre-arranged building blocks and a two-step synthetic route to rationally enable access a large unfolded tetrameric macrocycle, which is not accessible via conventional synthetic strategies. The obtained macrocycle hybrid cyclodiphosphazane macrocycle, cis-[μ-P(μ-NtBu)]2(μ-p-OC6H4C(O)O)]4[μ-P(μ-NtBu)]2 (4), displays an unfolded open-face cavity area of 110.1 Å2. Preliminary theoretical host–guest studies with the dication [MeNC5H4]22+ suggest compound 4 as a viable candidate for the synthesis of hybrid proto-rotaxanes species based on phosphazane building blocks.